Avaliação do processo de reparo ao redor de implantes de TiAlV com superfície usinada e modificada: estudo biomecânico em coelhos - Loureiro, Caroline [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In order to accelerate the early stages of the repair process around dental implants, reducing the period of osseointegration, various measures have been suggested, including the topographical modification of the implant surface. The proposition of this study was to evaluate the behavior of the interface formed between bone and implant on the machined surfaces (SU) and modified by sandblasting and acid etching, commercially available (SJA). Topographic characterization of surfaces by means of SEM-EDX system prior to experimental surgery was performed. Albinus Ten rabbits received 20 implants (Ti4Al6V) 4x10mm in surgical beds milled in the medial portion of the right and left tibias, each being an implant surface at each tibia randomly distributed. After placement of each implant was measured its coefficient stability by analyzing frequency by resonance. In periods 3 and 6 weeks the animals were anesthetized, and in vivo was again measured the coefficient of stability of the implant, followed by the biomechanical analysis by removal torque measurements. The values obtained were taken to the analysis of variance and t test Tukey. The SEM-EDX system showed differences between the surfaces analyzed. The average frequency of resonance measured by the SU were 48, 52, 52 ISQ respectively in the periods of 0, 3 and 6 weeks while group SJA to the average measures of resonance frequency were 50, 54, 55 respectively in the same periods. The average removal torque measurements in SU group were 10.6 and 13.9 N / cm, respectively in the periods 3 and 6 weeks, while for the group SJA average removal torque measurements were 19 and 17.4 N / cm in the same periods. There were no statistically significant differences (p <0.05) between the frequency measured by resonance SU and SJA in the analyzed periods. The SJA removal torque...

No intuito de acelerar as fases iniciais do processo de reparo ao redor de implantes dentários, diminuindo o período de osseointegração, várias medidas vêm sendo sugeridas, entre elas a modificação topográfica da superfície do implante. A proposição do presente trabalho foi avaliar o comportamento biomecânico da interface formada entre osso e implante diante das superfícies usinada (SU) e modificada por jateamento de óxido de alumínio seguido do condicionamento ácido, disponível comercialmente (SJA). Caracterização topográfica das superfícies por meio do sistema MEV-EDX previamente a cirurgia experimental foi realizada. Dez coelhos Albinus receberam aleatoriamente 20 implantes de 4x10mm em leitos cirúrgicos fresados na porção medial das tíbias direita e esquerda, sendo um implante de cada superfície em cada tíbia. Após instalação do implante foi mensurado o seu coeficiente de estabilidade por meio da análise de frequência por ressonância. Nos períodos de 3 e 6 semanas os animais foram anestesiados, e in vivo foi mensurado novamente o coeficiente de estabilidade do implante, seguido da análise biomecânica por meio de medidas do torque remoção. Os valores obtidos foram levados à análise de variância, e ao teste t de Tukey. O sistema MEV-EDX mostrou diferenças entre as superfícies analisadas. As medidas médias de frequência por ressonância no grupo SU foram 48, 52, 52 ISQ respectivamente nos períodos de 0, 3 e 6 semanas, enquanto para o grupo SJA foram de 50, 54, 55 respectivamente nos mesmos períodos. As medidas médias de torque de remoção no grupo SU foram 10,6 e 13,9 N/cm respectivamente nos períodos de 3 e 6 semanas, enquanto para o grupo SJA as medidas foram 19 e 17,4 N/cm nos mesmos períodos. Não houve diferenças estatisticamente significantes (p< 0,05) entre as medidas de frequência...
Keywords: Implantes dentários; Coelho; Osseointegração; Dental implants